Interventions from the transactional analysis in women who suffered from infidelity - Silva Cruz, Julio (2008)
This Transactional analysis provide powerful instruments allowing people to learn how to manage situation which could be painful. For these reasons, this paper emphasizes the importance of autonomy, in searching the person not to establish relationship bases on dependence.